Measuring Interoception: The CARdiac Elevation Detection Task - Ponzo, Sonia; Morelli, Davide; Suksasilp, Chatrin; Cairo, Massimo; Plans, David (Frontiers in Psychology, 2021)
Interoception has increasingly been the focus of psychiatric research, due to its hypothesised role in mental health. Existing interoceptive tasks are often burdensome and require specialised equipment, limiting their usage in vulnerable populations. We report on the development of the CARdiac Elevation Detection (CARED) task. Participants’ heart rate is recorded by a wearable device connected to a mobile application. Notifications are sent to participants’ mobile throughout the day over a period of 4 weeks. Participants are asked to state whether their heart rate is higher than usual, rate their confidence and describe the activity they were involved in when the notification occurred. Data (N=30) revealed that ⅓ of the sample was classified as interoceptive and that participants presented overall good insight into their interoceptive abilities. Given its ease of administration and accessibility, the CARED task has the potential to be a significant asset for psychiatric and developmental research.